Predictors of attack performance in high-level male volleyball players - Challoumas, D.; Artemiou, A. (International Journal of Sports Physiology and Performance, 2018)
Purpose: In volleyball, teams win the majority of points through attacks (spikes), and therefore attack effectiveness (AE) is one of the most important predictors of victory. Traditionally, greater vertical jump heights (VJH) and higher spike speeds (SS) have been thought to increase AE; however, relevant research is limited. The authors` aim was to assess the relationship of VJH and SS with AE, as well as identifying possible associations of demographic and anthropometric factors, including common volleyball injuries, with VJH, SS, and AE. Methods: A total of 22 male volleyball players from 2 teams in the top division of the Cypriot championship were included in the study. VJH was measured with the jump-and-reach test, SS was tested with a sports speed radar, and AE was calculated from performance reports of 4 matches between the 2 teams. Results: Statistically significant results included positive correlations between VJH and SS, percentage lean mass and SS, body-bone percentage and SS, frequency of volleyball practice and SS, and frequency of resistance training and SS. AE was found to increase with increasing age, while SS over 90 km·h-1 appeared to have a negative effect on AE. History of pain in the dominant shoulder and in the ankles/knees was associated with lower SS and higher VJH, respectively. Conclusions: Based on the findings and the existing literature, volleyball players and coaches are advised to focus on maximization of VJH and optimization of attack technique; recommendations to improve attack success are provided.